SARS-CoV-2: Virology and Drug Repurposing Approaches - Rahmasari, Ratika; Setiawan, Heri; Syahdi, Rezi Riadhi; Arifianti, Ayun; Irianti, Marina Ika; Sauriasari, Rani; Makau, Juliann Nzembi; Raekiansyah, Muhareva (Pharmaceutical Sciences and Research, 2020)
An emerging coronavirus, SARS-CoV-2, is the causative agent for the ongoing pandemic of coronavirus disease 2019 (COVID-19), which has caused a worldwide social and economic disruption. Currently, no antiviral drugs with proven clinical efficacy, or vaccines for its prevention. Therefore, to combat the pandemic of this novel coronavirus, new effective treatments are urgently needed. In the process of traditional drug development, developing new drugs from scratch is a time- consuming process, requires high-investment, and is a high-risk process, which is impractical to face the immediate global challenge of the SARS-CoV-2 pandemic. Drug repurposing strategy is one of the effective ways to quickly find a therapeutic agent for COVID-19 Existing medicines, which already have been tested and proven safe in humans might work for COVID-19 offering a potentially faster approach for the disease management. Here, we review h the latest research progress in epidemiology, viral genome, and life cycles of SARS-CoV-2. Further, we describe and discuss some promising drugs repurposed to target SARS-CoV-2 that are being evaluated in clinical trials.